Desenho metodológico para o ensino de físico-química em uma concepção de aprendizagem ativa - Rodrigues, Ciléia (2021)
In this work, we developed, implemented and evaluated the feasibility and effectiveness of a Methodological Design that was elaborated based on the conceptions of the Reversed Classroom, for the teaching of Physical Chemistry contents: Stoichiometric Calcium, Solutions and Thermochemistry. This branch of chemistry, in particular, is extremely procedural and requires a variety of activities for a better understanding of its concepts. The traditional form of teaching, most of the time, does not allow the performance of activities and problems in the classroom, due to lack of time, and these are destined to be held at home, which makes it difficult to discuss the concepts and clarify the doubts that arise. Allied to this scenario, the teacher faces a different profile of students, who were born in an era where the flow of information is constant and intense, which implies a different society with specific needs and which requires a transformation in education and in all individuals participating in the process. Therefore, active teaching methodologies, more specifically in the Reversed Classroom, have found the principles that can help transform the classroom dynamics of students of the 2nd grade high school of a state public school, through a methodology that makes this environment a space of discussion between peers and between students and teacher. With this, it is expected that students will be able to develop greater autonomy in their learning, making it more meaningful and based on interaction between individuals. For the elaboration, implementation and evaluation of the Methodological Design proposed in this study, the Education Design Research was used as a research methodology. The Methodological Design prepared for the teaching of Physical Chemistry is composed of four stages, which comprise Video Classes, Guiding Activities, Classroom Activities and Evaluative Activities. The results indicate that the Methodological Design proposed in this thesis is viable and effective for the discussion of the concepts of Physical Chemistry, enabling students to deconstruct the role of a passive listener for an active student, who effectively participates in the search and construction of knowledge, making him responsible not only for his learning, but for that of his colleague. This change of attitude of the individuals who participate in the process promoted a transformation in the dynamics of classroom classes, making the classroom a space where concepts are not only presented, but discussed from the perception of all, in an active and collaborative construction of knowledge.